ASEAN University Network in Enhancing Student Mobility: A case of Indonesia - Soejatminah, Sri (Journal of Interdisciplinary Studies in Education, 2018)
Internationalization of higher education pushes for more intensive regional collaborations as well as student mobility. There are a plethora of studies exploring student mobility patterns, but research on the transformative potential of regional mobility networks is limited. As the most predominant regional network of universities in Southeast Asia, ASEAN (Association of South East Asian Nations) University Network (AUN) commits to boosting student mobility in the region, and thus, can be conceived to be a deliberative space capable of expanding student mobility. This chapter examines the role of AUN in promoting student mobility within the ASEAN region. Indonesia’s engagement is used as a point of entry to assess the extent of policies and programs in encouraging student mobility in the ASEAN region. It shows that AUN has established regional quality assurance and credit transfer systems to promote credit student mobility across AUN member universities. In this regard, the implementation of Indonesian qualification framework has reinforced AUN in the operationalization of credit transfer system across the member universities. Similarly, the existing Indonesian quality assurance body has strengthened AUN in bridging collaborations for student mobility. Thus, the current state of credit student mobility across AUN member universities is shaped by not only by AUN but also Indonesian and higher education institutional policies and systems related to student mobility reflecting the various levels of players in the ASEAN region.